Karakteristik Penduduk Miskin di Papua Barat - Ludia Theresia Wambrauw; Ratna M. H. Gusti; Agus Irianto Sumule (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2018)
This research entitles Characteristics of Poor People in Papua Barat Province. The research aims are to describe poor people characteristics in Papua Barat, and to analyze some factors that influence poverty in Papua Barat Province. The research is conducted in Papua Barat Province by using data from Indonesia’s Statistics. Then a descriptive analysis method is used to describe the characteristics of poor households in Papua Barat and their contributing factors. The results showed that the percentage of poor people in Papua Barat has been decreasing from 2009 to 2016. The percentage of poverty is decreasing more in rural areas than in urban areas. The characteristics of the poor people are the number of household member is more than four people; have low level of education, majority live in remote areas and work in agricultural sector, less of them are migrants, and have no health issues. Based on those characteristics, the Papua Barat government should put attention in developing the agricultural sector and improving the social and economic infrastructures in rural areas.